Twice Applications of Laying Hens Manure Produced the Highest Yield of Organic Okra Pods (Abelmoschus esculentus L. Moench.) - Fhonna, Tasya Nurizki; Melati, Maya; Aziz, Sandra Arifin (Journal of Tropical Crop Science, 2023)
The optimal okra cultivation using organic fertilizers remains a subject of limited information. This study aimed to assess the impact of applying 18 t.ha-1 of laying hens' organic fertilizer on the morphological and physiological traits of the "Naila IPB" green okra variety. The study was conducted between September and December 2022 at the IPB organic experimental field at Cikarawang, Bogor, West Java, Indonesia. A randomized complete block design with a single factor namely frequency of organic fertilizer application, was employed. The factor consisted of four levels: no organic fertilization, 1-, 2-, and 3-times applications. The results demonstrated that a single application of organic fertilizer led to an increase in plant height at 5, 7, and 9 weeks after planting (WAP), leaf number at 5 WAP, root dry weight at 4 WAP, stem dry weight at 10 WAP, and an acceleration in the onset of flowering. This resulted in a flowering period lasting 29.6 days, with a total flowering duration of 69.33 days. In contrast, a two-times application of organic fertilizer resulted in elevated plant height at 11 WAP, an increased leaf number at 11 WAP, heightened leaf potassium content, a greater number of pods per plant, and a higher yield of young pod okra. These findings contribute to our understanding of the effects of organic fertilizer application frequency on the growth and yield of young pod okra, aiding in the formulation of improved cultivation strategies.